2016
DOI: 10.1002/2016gl069946
|View full text |Cite
|
Sign up to set email alerts
|

SMAP soil moisture drying more rapid than observed in situ following rainfall events

Abstract: We examine soil drying rates by comparing surface soil moisture observations from the NASA Soil Moisture Active Passive (SMAP) mission to those from networks of in situ probes upscaled to SMAP's sensing footprint. SMAP and upscaled in situ probes record different soil drying dynamics after rainfall. We modeled this process by fitting an exponential curve to 63 drydown events: the median SMAP drying timescale is 44% shorter and the magnitude of drying is 35% greater than in situ measurements. We also calculated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
77
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 107 publications
(106 citation statements)
references
References 39 publications
8
77
0
Order By: Relevance
“…Instead we use calculations of changes in surface soil moisture through time, which Shellito et al (2016b) showed to provide a similar depiction of soil drying as the exponential approach. Importantly, by analyzing simple soil drying rates we avoid introducing new uncertainties into our analysis associated with fitting an exponential decay model.…”
Section: P J Shellito Et Al: Controls On Surface Soil Drying Ratesmentioning
confidence: 99%
See 3 more Smart Citations
“…Instead we use calculations of changes in surface soil moisture through time, which Shellito et al (2016b) showed to provide a similar depiction of soil drying as the exponential approach. Importantly, by analyzing simple soil drying rates we avoid introducing new uncertainties into our analysis associated with fitting an exponential decay model.…”
Section: P J Shellito Et Al: Controls On Surface Soil Drying Ratesmentioning
confidence: 99%
“…However, continental-scale evaporation from soil is notoriously difficult to measure directly. Lysimeters and chamber measurements provide information over extremely small areas (∼ 10 m 2 or less) (e.g., Herbst et al, 1996;Stannard and Weltz, 2006). Soil drying rates determined from satellite-based observations can provide an estimate of surface evaporation rates on a large scale (McColl et al, 2017a).…”
Section: P J Shellito Et Al: Controls On Surface Soil Drying Ratesmentioning
confidence: 99%
See 2 more Smart Citations
“…Several processes have been developed by the scientific community to validate soil moisture remote sensing products from satellites, such as the Advanced Microwave Scanning Radiometer for the Earth Observing System (AMSR-E) [10,12,25], SMAP [26][27][28], and SMOS [2,6,16,17,24,29]. These remotely sensed data have been used to obtain drought indices with monitoring goals [10,12], including SMOS soil moisture data [1,5,8,30].…”
Section: Introductionmentioning
confidence: 99%